REPRODUCTION, FECUNDITY AND SEX RATIO OF THE GREEN TIGER PRAWN, PENAEUS SEMISULCATUS DE HAAN - Thomas, M M (Indian Journal of Fisheries, 2011)
Investigations on the reproduction, gonado-somatic index, fecundity and sex ratio of Penaeus semisulcatus were carried out at Mandapam Camp, from April, 1967 to March, 1969. Five stages of maturity could be differentiated depending on tlie colour of the ovarian lobes, the thickness of the ovary and the size of the ova. Female prawns with mature ovaries occurred throughout the year showing that they spawn continuously, the peak season being June to September and January to February. The gonado-somatic index exhibited a variation from 2.2 to 13.2. The minimum size at maturity in females was found to be 23 mm carapace length. The fecundity of the species was found to range between 51,605 and 6,60,904. There was no relation between the fecundity and the length of prawn, weight of prawn or weight of ovary. The samples examined contained more or less same number of males and females, although, during certain months the males were more in number while in other months the females were dominating.